Lived Religion as Reproductive Decision-Making Resource Among Romanian Women Who Use Abortion as Contraception - Pop, Cristina A. (Journal of religion and health, 2019)
This article draws upon qualitative ethnographic data collected between 2005 and 2013 in southern Romania among women who have been consistently using abortion as a contraceptive method. It particularly considers the role that lived religion might have played in some individuals' strategies to render abortion a justifiable practice. Over the last seven decades, Romanian women's experiences of abortion have often been at odds with both secular and religious regulations. This study shifts the perspective from the biopolitics and the bioethics of abortion toward women's own reproductive decision-making strategies in a context of enduring traditional patriarchy. It explores the fluid and pragmatic ways in which some Romanians use the notions of "God's will," "sin," "redemption," "afterlife," and "Godparenting" to redefine abortion as a partially disembodied reproductive event. As a reproductive decision-making resource, lived religion empowers women to navigate the lived complexities of conception and contraception.